Connected mechanical engineering curriculum through a fundamental learning integration platform - Feldhausen, Thomas (Kansas State University, 2017)
To keep students engaged in the learning process, educational engineering institutions need to enhance their curricula. Courses within an undergraduate curriculum need to be connected in a way that is meaningful and promotes student engagement through hands-on learning. Courses are currently designed like silos of knowledge with no connection between them, yet, there needs to be a realistic and practical tie between them. Prior research that addresses course integration, hands-on learning and student engagement has guided the development of this thesis. Building on prior research, a Fundamental Learning Integration Platform (FLIP) has been developed that uses a physical object to integrate traditionally mechanical engineering taught courses with the use of a single ubiquitous object. This learning platform has three desired outcomes: 1) it connects the entire curriculum, 2) it creates a physical connection between theoretical and practical engineering concepts, and 3) it engages and includes every student in the learning process. After identifying research to guide the development of the FLIP as well as identifying courses in a mechanical engineering curriculum, a desktop steam engine was developed and is shown that it is applicable to each course. This physical object acts as the FLIP. Ultimately, it will create a physical connection between theoretical and practical engineering concepts while integrating courses together and actively engaging each student in the learning process. Utilizing the same assessment methods used in the identified research, higher retention rates, increased passing rates of the Fundamentals of Engineering exam, and increased student inclusion in the classroom are all desired measurables of the FLIP. The results of this research have provided a well-developed FLIP that utilizes a physical object to increase student engagement while integrating traditional mechanical engineering courses together.
Keywords: Student engagement; Curriculum integration; Curriculum development; Physical object; Hands-on learning